"Everyone Deserves a Bit of Joy": A Case Study of the Royal New Zealand Ballet's Prison Program - Skorstengaard, Jana (Université d'Ottawa / University of Ottawa, 2021)
Art has a long and nuanced history within the context of the prison. Prisoners have utilized wall drawings, tattooing, journaling, and other forms of creative expression to break the monotony of prison life. Over time, art has evolved in the prison context and has been utilized by researchers, therapists, and teachers as a method of rehabilitation that falls outside of more conventional methods such as talk therapy, drug treatment, and anger management programs. Arts programming allows prisoners to express themselves in new and creative ways, as well as the ability to build new skills and foster better relationships with themselves and each other. A review of the literature discusses the negative effects of imprisonment on the body. As a result of the violent and incapacitating nature of being caged, prisoners become mirrors of the carceral space. Bodies become rigid, condensed, hunched, or even bulky in order to survive. Dance is an opportunity for prisoners to find freedom within the walls of a prison, as well as more tangible benefits such as improving posture, flexibility, and giving prisoners new ways to express themselves through movement. This can lead to improved self-esteem, a sense of accomplishment, and fostering better relationships with themselves and others. Using Foucault’s concept of docile bodies as well as Goffman’s theory dramaturgy, this research serves to fill in gaps in the literature around how dance impacts the body and emotional well-being. Through one-on-one interviews with members of the Royal New Zealand Ballet, this paper will examine dance’s ability to free the body and help prisoners find a sense of belonging and identity unrelated to their criminality.
Keywords: Royal New Zealand Ballet; Ballet; Dance; Prison dance; Criminalized populations; Arts-based initiatives; Docile bodies; Prisoners; Foucault; Goffman; Dramaturgy